Litopenaeus vannamei peritrophin interacts with WSSV and AHPND-causing V. parahaemolyticus to regulate disease pathogenesis. Issue 126 (July 2022) - Chen, Yi-Lun; Kumar, Ramya; Liu, Chun-Hung; Wang, Han-Ching
Abstract: Peritrophins are peritrophic membrane (PM) proteins that can interact with chitin fibers via chitin-binding domains. Peritrophins have essential roles in providing porosity and strength to the PM that lines the shrimp midgut. Acute hepatopancreatic necrosis disease (AHPND), caused by strains of V. parahaemolyticus, is known to initially colonize the shrimp stomach and simultaneously disrupt its structural barriers (e.g., cuticle or epithelial tissues) to reach the hepatopancreas. Although stomach and hepatopancreas were identified as target tissues involved in AHPND pathogenesis, our results indicated that peritrophin in peritrophic membrane has a crucial role in determining not only colonization of AHPND-causing bacteria but also their tissue distribution. As the interaction between Lv Peritrophin ( LvPT ) and WSSV (white spot syndrome virus) is not well understood, we noted that LvPT expression was upregulated in shrimp stomach challenged with either WSSV or AHPND. In an i n vitro pathogen binding assay, there was strong binding of recombinant LvPT WSSV and AHPND-causing V. parahaemolyticus, and various bacteria. Furthermore, dsRNA-mediated LvPT silencing inhibited WSSV gene expression and viral genome replication. However, downregulation of LvPT gene expression increased copies of AHPND-causing bacteria in shrimp digestive tract, and facilitated bacterial colonization in stomach. In conclusion, we speculated that LvPT might regulate bacterial colonization during AHPND, whereas in WSSV infection, LvPT silencing favored the host. Although recombinant LvPT had strong binding with WSSV, the precise role of LvPT in WSSV infection needs further investigation. These findings increased our understanding of host-pathogen interactions in AHPND and WSSV infection that can be applied in shrimp aquaculture for developing effective antibacterial and antiviral strategies. Highlights: A Peritrophin with 3 chitin-binding domains was identified from Litopenaeus vannamei. Recombinant LvPT had strong binding ability to WSSV, and AHPND-causing V. parahaemolyticus. Silencing LvPT in L. vannamei reduced WSSV replication. LvPT silencing increased colonization of AHPND-causing bacteria in shrimp digestive tract.